From myth to history - Yehoshuʿa, Avraham B. 1936-2022 (2004)
If we were to unravel the foundation of Jewish identity into its primary components, we would discover that beyond the religious commandments, beyond the various national sentiments, beyond the sense of belonging and connection to the Land of Israel and the Hebrew language, beyond certain historical and family memories that uniquely determine the Jewish identity of each individual, the common basis of all Jewish identities, in their various dosages and strengths, comprises several fundamental stories—stories that have shed any clear indicia of historical time and place and have become myths, metastories, which can no longer be changed, only interpreted. These myths, such as the binding of Isaac (the akedah), the story of the exodus and other bible stories, the stories of the destruction of the Temple (and recently, in a certain sense, the Holocaust), have become the infrastructural components of Jewish consciousness and identity, both religious and secular. They have served for millennia as effective ingredients in the preservation of the identity of many Jews, scattered among various lands and continents, in the midst of various peoples and religions and assorted civilizations, and for centuries without being specifically dependent on the clear historical context of a defined territory or language. These myths are the most primary basis for the existence of diaspora Jewish identity, which makes possible the preservation of Jewish identity “outside history,” in the famous phrase of Gershon Scholem, notwithstanding the terrible toll that this existence has taken on the Jewish people in the end. The power of these myths lies in the fact that one's connection to them can be immediate, in all places and at all times, and beyond their original linguistic form; this connection finds succinct expression in the sentence, “In every generation, a person is obligated to regard himself as if he himself left Egypt.”
Keywords: Morality; Faith; Myths; Judaism; Jewish Identity; philosophy of religion; Divinity; Jewish History; Innocence; Legendary places